Distribution and tritrophic associations of aphid parasitoids of the tribe Aphidiini (Aphidiinae: Braconidae: Hymenoptera) in India - Rajendra Singh (Arthropods)
The members of the tribes Aphidiini (Aphidiinae: Braconidae: Hymenoptera) are exclusively koinobiont aphid parasitoids and are widely distributed. Some of the species of parasitoids have been successfully used in the biological control of aphids worldwide. The Aphidiini comprises 70 species of parasitoids in India parasitizing 165 species of aphids in 24 states and 2 union territories. Aphidius is the highly speciose genus in India, comprising 35 species parasitizing 137 species of aphids feeding on 209 species of host plants (excluding unidentified ones) distributed in 20 states and 2 union territories, followed by Pauesia (19 species, 14 host plants, 7 states, and one union territory), and other genera comprise only 1-2 species. Among the parasitoids, Aphidius matricariae Haliday is highly polyphagous, parasitizing 47 species of aphids infesting 83 species of plants, followed by Diaeretiella rapae (McIntosh) (27 species of aphids feeding on 58 species of plants) and Aphidius colemani Viereck (22 species of aphids feeding on 42 species of plants). Twenty eight species of aphid parasitoids recorded in India are monophagous, and 63 species of the parasitoids parasitize less than 10 species of aphids. More than half of the parasitoid species were recorded in Jammu and Kashmir (36 species), followed by Meghalaya (31 species), West Bengal (26 species), Manipur (24 species), Sikkim (24 species), Uttarakhand (22 species), Himachal Pradesh (20 species), and less than 20 species in other states. The maximum tri-trophic associations (parasitoid-host aphid-host plant, triplet) were observed in Jammu and Kashmir (191 triplets), followed by Manipur (122 triplets), Uttar Pradesh (90 triplets), Meghalaya (81 triplets), Himachal Pradesh (80 triplets), Uttarakhand (78 triplets), Sikkim (64 triplets), and less than 50 triplets in other states.